Evaluation of the diagnostic efficacy of salivary malondialdehyde among smokers and nonsmokers with periodontal disease: A case-control study - Haneen Fahim Abdulqader - Maha Sh. Mahmood ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Reactive oxygen species (ROS) are molecules that are produced by a variety of metabolic processes that can lead to oxidative stress and subsequent direct or indirect tissue damage, are linked to the pathogenesis of the majority of inflammatory processes and result in periodontal disorders. Lipid peroxidation product malondialdehyde (MDA) caused by ROS can lead to tissue injury. The aim of this study was to assess and compare the concentrations of malondialdehyde (MDA) in periodontal health and periodontal disease in nonsmokers and smokers, and to establish its usefulness as diagnostic indicators for periodontal disease.125 male patients were categorized as control: 25 healthy nonsmokers,25 nonsmokers with gingivitis,25 smokers with gingivitis, 25 nonsmokers with periodontitis and 25 smokers with periodontitis. For at least 10 minutes, 2ml of unstimulated saliva was collected. Periodontal clinical parameters (PI, BOP, PPD and CAL) were recorded to assess each subject's periodontal health. An enzyme-linked immunosorbent assay measured salivary MDA levels. All groups had higher levels of salivary MDA (P < 0.05) when compared to the healthy controls, except for the nonsmoker periodontitis group was not statistically different from the control group; however, smoker groups had higher MDA levels than nonsmoker groups. With the limitations of this case-control study, it may be suggested that the oxidative stress biomarker MDA was higher in periodontal diseases associated with risk factors such as smoking and this biomarker has the potential to be employed as a diagnostic biomarker for periodontal diseases.